Run for your heart - Siti Sarah, Mohamad Rajimi (2017)
In conjunction with the World Heart Day Celebration 2017, the Secretariat for Genesis of Healthy Students (GENESIS) in collaboration with Student Affairs & Alumni Department (JHEPA), State Health Department (JKNP), UMP Health Center and the Paya Besar Students Club held the World Heart Day Closing Ceremony and Balloon Run 2017 at the Chancellor Square.